Impact of protective barriers on groundwater quality - Wysocka, Małgorzata Ewa; Zabielska-Adamska, Katarzyna (International Conference “Environmental Engineering”, 2017)
The storage yard’s leak roof protection should be achieved by means of independent protective barriers in the form of geological barriers, artificial sealing layers, mineral soil liners and covers, as well as sidewall sealing. Some years ago, construction and exploitation of landfill sites in Poland took place without any guidelines and legal regulations. Landfills, especially situated in rural areas, were quite often constructed directly on the grounds, e.g. in former aggregate excavations, without any protection. Examples of the municipal landfills, located in the sites of adverse geo logical conditions were presented in this paper. The effect of existence or absence of geological barriers on the ground water quality was carried out. In tested landfills, higher concentrations of groundwater pollution indicators were found in landfill monitoring wells located on the outlet of these waters, in comparison to the landfill monitoring wells located on their supply. In the case of the landfills situated directly on the soils of high hydraulic conductivity, the indicators of negative influence of deposited landfills increased even after the closing of the landfill sites. Subsurface water earing layer is a kind of “indicator” giving information about the harmful effect of landfills on the environment, and the need to take remedial actions.
Keywords: landfill of municipal waste; protective barriers; geological barrier; groundwater quality